2014
DOI: 10.5348/ijcri-201555-ra-10010
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants and their implication in oral health and general health

Abstract: Introduction: Oxygen is extremely crucial for the existence of higher organisms. As the saying goes too much of even the best is awful. High and soaring concentration of oxygen are found to be toxic, and can damage tissues. Free radicals can adversely alter lipids, proteins and DNA and have been implicated in aging and in number of human diseases. Lipids are highly prone to free radical damage resulting in lipid peroxidation that can lead to adverse alterations. Free radical damage to protein can result in los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
4
0
1
Order By: Relevance
“…This effect is also attributed to the major role of bioactive compounds present in the added by-products as natural source of antioxidants which are responsible for health promoting action 28 . Other authors 41 , 42 reported that high concentration of polyphenols implies that the antioxidants of the by-products significantly increase because of its capacity to block free radicals. This relationship between polyphenols and antioxidants was also reported by others 43 , 44 .…”
Section: Discussionmentioning
confidence: 98%
“…This effect is also attributed to the major role of bioactive compounds present in the added by-products as natural source of antioxidants which are responsible for health promoting action 28 . Other authors 41 , 42 reported that high concentration of polyphenols implies that the antioxidants of the by-products significantly increase because of its capacity to block free radicals. This relationship between polyphenols and antioxidants was also reported by others 43 , 44 .…”
Section: Discussionmentioning
confidence: 98%
“…However, the specific harmful effects of antioxidants on the oral area have not been thoroughly addressed in studies yet. It is important to balance antioxidant intake and consult healthcare professionals to avoid adverse effects on oral health [ 29 ].Topical antioxidant remedies can be beneficial in reducing free radicals or reactive oxygen species in the oral environment [ 30 ].…”
Section: Overview On Oxidative Stress Cancer and Antioxidantsmentioning
confidence: 99%
“…Supplementing laying hens' diet with 9% PSM promotes the enrichment with antioxidant compounds in egg white and yolks. This is a beneficial result, considering the fact that antioxidant A c c e p t e d A r t i c l e compounds act synergistically with each other, providing a protective effect against eventual lipid peroxidation [32], especially in eggs with high PUFA concentration. For this reason, simultaneously enrichment of eggs with polyphenol and antioxidant compounds was suggested to decrease fatty acid oxidation and provide a good source of dietary antioxidant [33] which have been associated with beneficial effect on human health.…”
Section: Effect Of Pumpkin Seed Meal On Total Antioxidant Compounds In Eggsmentioning
confidence: 99%